TESS Observations of Cepheid Stars: First Light Results - Plachy, E.; Pál, A.; Bódi, A.; Szabó, P.; Molnár, L.; Szabados, L.; Benkő, J. M.; Anderson, R. I.; Bellinger, E. P.; Bhardwaj, A.; Ebadi, M.; Gazeas, K.; et al. (The Astrophysical Journal Supplement Series, 2021)
We present the first analysis of Cepheid stars observed by the TESS space mission in Sectors 1-5. Our sample consists of 25 pulsators: ten fundamental mode, three overtone and two double-mode classical Cepheids, plus three type II and seven anomalous Cepheids. The targets were chosen from fields with different stellar densities, both from the Galactic field and from the Magellanic System. Three targets have 2 minutes cadence light curves available by the TESS Science Processing Operations Center: for the rest, we prepared custom light curves from the full-frame images with our own differential photometric FITSH pipeline. Our main goal was to explore the potential and the limitations of TESS concerning the various subtypes of Cepheids. We detected many low-amplitude features: weak modulation, period jitter, and timing variations due to light-time effect. We also report signs of nonradial modes and the first discovery of such a mode in an anomalous Cepheid, the overtone star XZ Cet, which we then confirmed with ground-based multicolor photometric measurements. We prepared a custom photometric solution to minimize saturation effects in the bright fundamental-mode classical Cepheid, β Dor with the lightkurve software, and we revealed strong evidence of cycle-to-cycle variations in the star. In several cases, however, fluctuations in the pulsation could not be distinguished from instrumental effects, such as contamination from nearby sources, which also varies between sectors. Finally, we discuss how precise light-curve shapes will be crucial not only for classification purposes but also to determine physical properties of these stars.
Keywords: Astrophysics - Solar and Stellar Astrophysics; Cepheid variable stars; Stellar photometry; Stellar pulsations